The dinosaur book - Woodward, John, 1954- (DK Publishing, 2018)
Presents a visual guide to dinosaurs of all the prehistoric eras, with over 1,000 images and hundreds of fun facts and trivia about the world of dinosaurs, including their size, where they lived, how they hunted or defended themselves, and what they ate. Includes a glossary.